2021
DOI: 10.3390/cancers13215453
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of HSP70/HSF1 Axis Abrogates In Vitro Ibrutinib-Resistance in Chronic Lymphocytic Leukemia

Abstract: The Btk inhibitor ibrutinib has significantly changed the management of chronic lymphocytic leukemia (CLL) patients. Despite its clinical efficacy, relapses occur, and outcomes after ibrutinib failure are poor. Although BTK and PLCγ2 mutations have been found to be associated with ibrutinib resistance in a fair percentage of CLL patients, no information on resistance mechanisms is available in patients lacking these mutations. The heat shock protein of 70 kDa (HSP70) and its transcription factor heat shock fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…We ourselves used resveratrol, a natural polyphenol provided with anti-cancer properties through the modulation of different kinases (i.e., it inhibits Akt and activates Erk1/2), thus inducing the death of CLL cells by reducing HSP70 and HSF1 levels. Due to low bioavailability and poor potency of this molecule, other inhibitors with a structure and action like resveratrol, namely pterostilbene, triacetylresveratrol and honokiol, have been used and have been shown to be significantly effective in inducing apoptosis in CLL cells at concentrations lower than that used for resveratrol [ 99 ]. This approach that indirectly downmodulates HSP70, aims at reducing the unpredictable off-target effects that the direct inhibition of HSP70 protein have shown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We ourselves used resveratrol, a natural polyphenol provided with anti-cancer properties through the modulation of different kinases (i.e., it inhibits Akt and activates Erk1/2), thus inducing the death of CLL cells by reducing HSP70 and HSF1 levels. Due to low bioavailability and poor potency of this molecule, other inhibitors with a structure and action like resveratrol, namely pterostilbene, triacetylresveratrol and honokiol, have been used and have been shown to be significantly effective in inducing apoptosis in CLL cells at concentrations lower than that used for resveratrol [ 99 ]. This approach that indirectly downmodulates HSP70, aims at reducing the unpredictable off-target effects that the direct inhibition of HSP70 protein have shown.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests the involvement of HSP70 in mechanisms of drug-resistance. Moreover, we demonstrated that the use of HSP70/HSF1 axis inhibitors (i.e., resveratrol, honokiol, pterostilbene, and triacetyl-resveratrol), at different levels, could represent a novel rational therapeutic approach to overcome ibrutinib resistance in those patients who relapsed after this treatment [ 99 ]. Beside HSP70 itself, the role of its co-chaperone BAG3, has been characterized in CLL.…”
Section: Hsp70 and Its Targeting In Onco-hematological Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Written informed consent according to the Declaration of Helsinki and ethical approval were obtained. Normal and leukaemic B cells have been obtained as previously detailed 23 . Cells were cultured in RPMI 1640 medium (Thermo Fisher Scientific) with 2% FBS and 5% Penicillin/Streptomycin (Euroclone) at 2 × 10 6 /mL and incubated at 37°C in a humidified atmosphere containing 5% CO 2 with or without: 5 μM Defactinib, 50 μM calpeptin, 5 μM Bafetinib (Selleckchem), 2.5 and 5 mM Calcium Lactate (Sigma‐Aldrich) for 12 h or 24 h; with 10 μg/mL IgM or IgD for 5′ and 3′ respectively, according to the different experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Apoptosis was assessed using the Annexin V Apoptosis Detection Kit (Valter Occhiena S.r.l.) as previously described 23 and calcium (Ca ++ ) mobilization has been performed as detailed in Martini et al 24 HS1 and cortactin were analysed in CD19+/CD5+ cells with anti‐HS1 AlexaFluor®647 (cell signalling) and anti‐cortactin AlexaFluor®488 (Merck Millipore). Before staining, cells were fixed and permeabilized with FIX & PERM cell permeabilization kit for 10 min each at room temperature (Invitrogen; Thermo Fisher Scientific, Inc.).…”
Section: Methodsmentioning
confidence: 99%